Characterisation of nano-scale amylose-lipid complexes isolated from teff and maize starches during pasting, and their application as a fat replacer in margarine - Emmambux, Mohammad Naushad (University of Pretoria, 2014)
Thesis (PhD (Food Science))--University of Pretoria, 2013.